2007
DOI: 10.1128/jb.00896-07
|View full text |Cite
|
Sign up to set email alerts
|

CheX in the Three-Phosphatase System of Bacterial Chemotaxis

Abstract: Bacterial chemotaxis involves the regulation of motility by a modified two-component signal transduction system. In Escherichia coli, CheZ is the phosphatase of the response regulator CheY but many other bacteria, including Bacillus subtilis, use members of the CheC-FliY-CheX family for this purpose. While Bacillus subtilis has only CheC and FliY, many systems also have CheX. The effect of this three-phosphatase system on chemotaxis has not been studied previously. CheX was shown to be a stronger CheY-P phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
(51 reference statements)
5
18
0
Order By: Relevance
“…CheA is included in the assay because of the instability of CheY-P, which requires its in situ production (11,14,42,43). FliY does not affect CheA autophosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CheA is included in the assay because of the instability of CheY-P, which requires its in situ production (11,14,42,43). FliY does not affect CheA autophosphorylation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The supernatant was used for SDS-PAGE analysis. To demonstrate the binding of various constructs of FliY (100 M) to CheY (75 M) and CheY-P (75 M), pulldown assays were performed with His-tagged proteins as described previously (42,43) with minor modifications. The samples that required phosphorylation of CheY, 20 mM acetyl phosphate (Sigma-Aldrich) in the presence of 20 mM MgCl 2 ⅐6H 2 O was added for incubation and wash steps to the binding buffer to ensure complete phosphorylation of CheY.…”
Section: Methodsmentioning
confidence: 99%
“…CheD binds to both the receptor and CheC in order to play a role in adaptation (23,24,32). Other work has suggested that CheD protein levels in the cell may be linked to the presence of CheC and perhaps other proteins (31).…”
Section: Quantitative Immunoblots Of the Soluble Signaling Proteinsmentioning
confidence: 99%
“…For each motif, the conserved glutamate and asparagine are one helical turn apart on a solvent exposed alpha helix. Mutagenesis studies (15,17,18) suggest that the (E-X 2 -N) motif mediates catalysis. The (E-X 2 -N) motifs in CheC and CheX appear comparable to the structurally unrelated CheZ phosphatase, whose active site acid and amide residues Asp143 and Gln147 are also separated by a single helical turn (9).…”
mentioning
confidence: 99%